Domestic and international creative tourists in Portugal: Insights for practitioners - Serra, Jaime (2022)
Within the project CREATOUR (Creative Tourism Destination Development in Small Cities and Rural Areas), we developed a detailed questionnaire for participants in the creative tourism pilot activities organized within the project, which was applied by the 40 participating organizations as they conducted their pilot activities in 2017, 2018, and 2019.